Bridging the Skills Gap and Tackling Unemployment of Vocational Graduates Through Partnerships in Nigeria - Ayonmike, Chinyere Shirley; Okeke, & Benjamin Chukwumaijem (Journal of Technical Education and Training, 2016)
The level of skills possessed by vocational education graduates for employment has been a worrisome issue in Nigeria. In fact the representatives of labour markets tagged graduates from Nigerian universities as half-baked perceiving these graduates as lacking in employable skills, making them unemployable. The purpose of this study is to ascertain how partnerships between industries and vocational institutions can be a tool to bridge the skills gap and unemployment of vocational education graduates in Nigeria. Two research questions guided the study, and the research design used was the descriptive survey research design. The population of the study was 212 vocational education lecturers from seven selected universities owned by the government in Southern Nigeria. Random sampling technique using balloting was used to select 106 vocational educators. The instrument for data collection was a questionnaire developed by the researcher and was content and face validated by three vocational education lecturers. The questionnaire was administered to 10 vocational education lecturers and its reliability was estimated to be 0.73 using the Cronbach Alpha technique. Data collected were analysed using simple frequency count and percentage, and any response that has the highest frequency and percentage was recorded as the overall remark. The study revealed that industries and institutions partnerships will help to bridge the skills gap and reduce unemployment of vocational education graduates in Nigeria through workplace partnership like resource sharing, staff exchange and the establishment of vocational skills exhibition centres amongst others. Based on the findings of the study, it was recommended that industries, government and institutions should establish partnership that will help to enhance the skills and chances of employment of vocational education graduates in Nigeria.